Considering the State and Status of Internationalization in Western Higher Education Kinesiology. (3rd April 2021) - Culp, Brian; Lorusso, Jenna; Viczko, Melody
ABSTRACT: While internationalization is among the top strategic priorities of universities and colleges globally, research into the expanse of internationalization in the kinesiology discipline is not well researched. Given this gap, critical consideration of the state and status of the phenomenon is needed. Knowing more about what is being done in the name of internationalization within kinesiology and reflecting on how those actions and outcomes are aligned, or not, with key theoretical guidance is necessary in order to plan for improvement accordingly. For these reasons, this paper first provides a primer on internationalization in higher education, including how the phenomenon has come to be defined as well as key contemporary critiques associated with it. In particular, we highlight Beck's (2012) theoretical concept of 'eduscape' to critically consider the influences of globalization on internationalization within higher education kinesiology as well as Khoo, Taylor, and Andreotti's (2016) principles of intelligibility, dissent, and solidarity to consider the ways kinesiology scholars engage critically with internationalization processes. Presented next is a review of the kinesiology literature that is explicitly focused on internationalization. Then, the results of a pilot survey into the views of National Association for Kinesiology in Higher Education (NAKHE) members and other Western kinesiology scholars on internationalization is reported next. The paper concludes with recommendations as to how NAKHE and the broader community of Western kinesiology scholars might best navigate internationalization moving forward. We recommend the complexity-informed and principle-driven approach of inclusive leadership as a means of pursuing cognitive justice in the 21st century.